Increased RTN3 phenocopies nonalcoholic fatty liver disease by inhibiting the AMPK–IDH2 pathway - Hao Huang; Shuai Guo; Ya‐Qin Chen; Yu‐Xing Liu; Jie‐Yuan Jin; Yun Liang; Liang‐Liang Fan; Rong Xiang (MedComm, 2023)
Abstract Reticulon 3 (RTN3), an endoplasmic reticulum protein, is crucial in neurodegenerative and kidney diseases. However, the role of RTN3 in liver tissues has not been described. Here, we employed public datasets, patients, and several animal models to explore the role of RTN3 in nonalcoholic fatty liver disease (NAFLD). The underlying mechanisms were studied in primary hepatocytes and L02 cells in vitro. We found an increased expression of RTN3 in NAFLD patients, high‐fat diet mice, and oxidized low‐density lipoprotein‐treated L02 cells. The RTN3 transgenic mice exhibited the phenotypes of fatty liver and lipid accumulation. Single‐cell RNA sequencing analysis indicated that increased RTN3 might induce mitochondrial dysfunction. We further showed this in primary hepatocytes, the L02 cell line, and the Caenorhabditis elegans strain. Mechanistically, RTN3 regulated these events through its interactions with glucose‐regulated protein 78 (GRP78), which further inhibited the adenosine 5 monophosphate‐activated protein kinase (AMPK)–isocitrate dehydrogenase 2 (IDH2) pathway. In the end, knockout of RTN3 relieved fatty liver and mitochondrial dysfunction. Our study indicated that RTN3 was important in NAFLD and lipid catabolism and that an increase in RTN3 in the liver might be a risk factor for nonalcoholic steatohepatitis and NAFLD.